Group project information system - Chong, Ka An (2017)
In most of my time doing project during my course of studying, it is inevitable to user different software tools such Microsoft Word, Microsoft Excel and Web for project management. More than often we have to different software to edit our work then share via website such as dropbox. However, for project management related stuff this way of working is not user-friendly. Despite having to use different software to access the minutes and backlog, it is also not easy to retrieve and back track any project management decisions done previously. Although there is various project management software in the market, it is overly complex for the demand of the project assigned during class. Furthermore, the system is not developed and does not provide the professor with the necessary privilege and convenience to access all the data. This result in difficulty of professor using those systems to assess the student’s project management. The report begins by researching on the pro and cons of other system. After which it research on the most suitable tools needed to develop the desired integrated system. A web interface is chosen as it can be access from any platform which support web browsing. The system is developed using bootstrap framework and JavaScript as front end. PHP, MySQL and Apache as back end system. The system allows for integration of the meeting minutes and backlog. It also allows users to back track past decisions made. Surveys was done with students who took similar modules and experience the inconvenience of without an integrated system. Positive feedback on the integration system. There are also a number of improvements suggested that can be done to improve the system.